Effect of perioperative esketamine use on emergency delirium in children undergoing tonsillectomy and adenoidectomy: a systematic review and meta-analysis of randomized controlled trials - Junfeng Liu; Jinming Liu; Hong Sun; Xue Cheng; Chunhui Wang; Daoyun Lei; Chao Han (Frontiers in Medicine)
BackgroundEmergence delirium(ED) is a common postoperative complication in children undergoing tonsillectomy and adenoidectomy under general anesthesia. There is no high-quality evidence on the relationship between esketamine and ED. The systematic review and meta-analysis was performed to investigate the effect of perioperative esketamine use on ED in children undergoing tonsillectomy and adenoidectomy.MethodWe searched Embase, The Cochrane Library, PubMed, MEDLINE, Web of Science, China National Knowledge Infrastructure (CNKI), WanFang, VIP, and SinoMed from inception to 1 September, 2024. Two evaluators identified randomized controlled trials comparing perioperative use of esketamine with placebo or other drugs in children undergoing tonsillectomy and adenoidectomy. Incidence of ED was the primary outcome of the study. Data synthesis was performed by using Review Manager 5.4 software.ResultsTwenty-three relevant studies involving a total of 1,996 children were identified. Perioperative use of esketamine reduced the incidence of ED in children undergoing tonsillectomy and adenoidectomy (RR = 0.33, 95% CI: [0.25, 0.44], p < 0.00001, I2 = 0%). Scores of ED were lower in the esketamine group than in the control group (SMD = -1.20, 95% CI: [−1.56,-0.84], p < 0.00001, I2 = 88%). Children in the esketamine group have lower postoperative pain scores (SMD = -0.51, 95% CI: [−0.80,-0.39], p < 0.00001, I2 = 74%). Esketamine was also associated with a lower incidence of adverse events (RR = 0.75, 95% CI: [0.57, 0.99], p = 0.04, I2 = 62%). We also found that the use of esketamine reduced the length of stay in the post-anesthetic care unit (PACU) but had no effect on the time to extubation.ConclusionPerioperative use of esketamine could significantly reduce the incidence of ED in children undergoing tonsillectomy and adenoidectomy. However, the optimal dose and timing of esketamine administration for preventing ED remains to be explored.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=558560, PROSPERO: CRD42024558560.